The Role of Rosmarinic Acid on the Bioproduction of Gold Nanoparticles as Part of a Photothermal Approach for Breast Cancer Treatment - Ferreira-Gonçalves, Tânia (2022)
Breast cancer is a high-burden malignancy for society, whose impact boosts a continuous search for novel diagnostic and therapeutic tools. Among the recent therapeutic approaches, photothermal therapy (PTT), which causes tumor cell death by hyperthermia after being irradiated with a light source, represents a high-potential strategy. Furthermore, the effectiveness of PTT can be improved by combining near infrared (NIR) irradiation with gold nanoparticles (AuNPs) as photothermal enhancers. Herein, an alternative synthetic method using rosmarinic acid (RA) for synthesizing AuNPs is reported. The RA concentration was varied and its impact on the AuNPs physicochemical and optical features was assessed. Results showed that RA concentration plays an active role on AuNPs features, allowing the optimization of mean size and maximum absorbance peak. Moreover, the synthetic method explored here allowed us to obtain negatively charged AuNPs with sizes favoring the local particle accumulation at tumor site and maximum absorbance peaks within the NIR region. In addition, AuNPs were safe both in vitro and in vivo. In conclusion, the synthesized AuNPs present favorable properties to be applied as part of a PTT system combining AuNPs with a NIR laser for the treatment of breast cancer.